CHAC1: a master regulator of oxidative stress and ferroptosis in human diseases and cancers - Sun, Jiasen; Ren, Hui; Wang, Jiawen; Xiao, Xiang; Zhu, Lin; Wang, Yanyan; Yang, Lili (Frontiers in Cell and Developmental Biology, 2024)
CHAC1, an essential regulator of oxidative stress and ferroptosis, is increasingly recognized for its significant roles in these cellular processes and its impact on various human diseases and cancers. This review aims to provide a comprehensive overview of CHAC1's molecular functions, regulatory mechanisms, and effects in different pathological contexts. Specifically, the study objectives are to elucidate the biochemical pathways involving CHAC1, explore its regulatory network, and discuss its implications in disease progression and potential therapeutic strategies. As a γ-glutamyl cyclotransferase, CHAC1 degrades glutathione, affecting calcium signaling and mitochondrial function. Its regulation involves transcription factors like ATF4 and ATF3, which control CHAC1 mRNA expression. CHAC1 is crucial for maintaining redox balance and regulating cell death pathways in cancer. Its elevated levels are associated with poor prognosis in many cancers, indicating its potential as a biomarker and therapeutic target. Additionally, CHAC1 influences non-cancerous diseases such as neurodegenerative and cardiovascular disorders. Therapeutically, targeting CHAC1 could increase cancer cell sensitivity to ferroptosis, aiding in overcoming resistance to standard treatments. This review compiles current knowledge and recent discoveries, emphasizing CHAC1's vital role in human diseases and its potential in diagnostic and therapeutic applications.